Dichotomous Roles of Programmed Cell Death 1 on HIV-Specific CXCR5+ and CXCR5− CD8+ T Cells during Chronic HIV Infection - Jiao, Yan-Mei; Yang, Hong-Ge; Huang, Hui-Huang; Tu, Bo; Xing, Shao-Jun; Mao, Lin; Xia, Wei; He, Ran; Zhang, Ji-Yuan; Xu, Ruo-Nan; Jin, Lei; Shi, Ming; et al. (Frontiers in Immunology, 2017)
Background: CXCR5+CD8+T cells have been demonstrated to play an important role in the control of chronic viral replication; however, the relationship between CXCR5+CD8+T cells, HIV disease progression, and PD-1 expression profile on CXCR5+CD8+T cells during HIV infection remain poorly understood. Methods: We enrolled a total of 101 HIV patients, including 62 typical progressors (TPs), 26 complete responders (CRs), and 13 immune non-responders (INRs). Flow cytometric analysis, immunohistochemical staining, and relative function (i.e., cytokine secretion and PD-1 blockade) assays were performed to analyze the properties of CXCR5+CD8+T cells. Results: HIV-specific CXCR5+CD8+T cells in the peripheral blood and distribution of CXCR5+CD8+T cells in the lymph node (LN) were negatively correlated with disease progression during chronic HIV infection. PD-1 was highly expressed on CXCR5+CD8+T cells and positively associated with peripheral CD4+ T cell counts. Functionally, IFN-γ and TNF-α production of CXCR5+CD8+T cells were reduced by PD-1 pathway blockade, but the production of IFN-γ and TNF-α from CXCR5-CD8+T cells increased in response to TCR stimulation. Interestingly, PD-1 expression was constantly retained on CXCR5+CD8+T cells while significantly decreased on CXCR5-CD8+T cells after successful antiretroviral treatment in chronic HIV-infected patients. Conclusions: PD-1+CXCR5+CD8+T cells are functional cytotoxic T cells during chronic HIV infection. PD-1+CXCR5+CD8+T cells may represent a novel therapeutic strategy for the disease.